Counter-Realities. Impulses for a New Didactics of Literary History - Lorek, Karsten (Journal of Letters, 2018)
The article aims to give a fresh impetus to the didactics of literary history. For decades literary history has been criticized by literary scholars and educationalists: Poststructuralist and deconstructivist theories often consider it obsolete, and the didactics of literature emphasizes the difficulty of operationalizing, in accordance with a competence-oriented education, a specific literary-historical competence. Following, more or less implicitly, literary theories such as New Historicism, this article points out the remaining or even growing relevance of literary history within language arts and philologies in general, but specifically within German studies abroad. Teaching literary history is conceptualized as highlighting the cultural implications of the text (instead of teaching literary or historical eras), thus the understanding of a text remains incomplete without recognizing these social and historical implications. The article outlines the crucial role the cultural context plays in dealing with literary texts by focusing on eight competences (presented in pairs): understanding otherness (Fremdverstehen) and identity competence; critical judgment and argumentation competence; differentiated text comprehension and analytical thinking; creative thinking and aesthetic sensibility. Furthermore, this concept of teaching literary history is strongly linked to intermediality studies. It eventually calls for new curricula.